Al-Radd al-jamil : a fitting refutation of the divinity of Jesus - Ghazzālī, 1058-1111. (The History of Christian-Muslim Relations, 2016)
al-Radd al-jamīl attributed to al-Ghazālī (d. 1111) is the most extensive and detailed refutation of the divinity of Jesus by a Muslim author in the classical period of Islam. Since the discovery of the manuscript in the 1930's scholars have debated whether the great Muslim theologian al-Ghazālī was really the author. This is a new critical edition of the Arabic text and the first complete English translation. The introduction situates this work in the history of Muslim anti-Christian polemical writing. Mark Beaumont and Maha El Kaisy-Friemuth argue that this refutation comes from an admirer of al-Ghazālī who sought to advance some of his key ideas for an Egyptian audience.